Inductance Simulator Based on Dual Controlled CMOS Voltage Differencing Current Conveyor - Jerabek, J.; Sotner, R.; Prokop, R.; Kledrowetz, V.; Kartci, A.; Ayten, U. E. (IEEE, 2016)
The voltage differencing current conveyor (VDCC) based lossless/lossy inductance simulator with the advantage of extended (i.e. dual-controlled) range of equivalent inductance value and possibility of reconfiguration of polarity is presented in this study. These unconventional features are available because of newly designed CMOS structure of VDCC element. VDCC was fabricated lately in I2T100 0.7 um technology. Relevant VDCC-based inductance simulators are compared briefly with attention to controllability of inductance value especially. Theoretical expectations are compared with experimental results of an inductance simulator prototype obtained in laboratory measurements of proposed circuit based mainly on VDCC chip and its unique features are provided.
Keywords: Computer Science; Engineering